Nickel addition to optimize the hydrogen storage performance of lithium intercalated fullerides. (June 2020) - Aramini, Matteo; Magnani, Giacomo; Pontiroli, Daniele; Milanese, Chiara; Girella, Alessandro; Bertoni, Giovanni; Gaboardi, Mattia; Zacchini, Stefano; Marini, Amedeo; Riccò, Mauro
Graphical abstract: Highlights: We report different synthesis for the addition of transition metals to lithium fullerides. Fullerene hydrogenation takes place on H2 absorption of Ni decorated fullerides. The addition of Ni induces a remarkable increase in H2 storage and absorption kinetics. Ni particle size control achieves destabilization of the hydrofullerene molecules. Abstract: The addition of transition metals to alkali intercalated fullerides proved to enhance their already good hydrogen absorption properties. Herein we present a study based on two different synthetic strategies, allowing the addition of nickel as aggregates with different size to the lithium fulleride Li6 C60 : the former is based on the metathesis of nickel chloride, while the latter on the thermal decomposition of nickel carbonyl clusters. The hydrogen-storage properties of the obtained materials have been investigated with manometric and calorimetric measurements, which indicated a clear enhancement of the final absorption value and kinetics with respect to pristine Li6 C60, as a consequence of nickel surface catalytic activity towards hydrogen molecules dissociation. We found up to 10 % increase of the total H2 weight % absorbed (5.5 wt% H2 ) in presence of Ni aggregates. Furthermore, the control of the transition metal particles size distribution allowed reducing the hydrogen desorption enthalpy of the systems.